Enhancing the competitiveness of auto-parts enterprises: The case of proton’s suppliers - Mohd Rosli Mohamad (Universiti Malaya, 2010)
The launch of the national car project provided greater opportunities for local enterprises to be involved in the auto-parts making industry. However, the unprecedented pace of globalization, trade liberalization and capital movement in recent times has posed great challenges for local enterprises, particularly auto-parts suppliers to compete in the open market. Public-private partnership would be one of the ways to mitigate the unexpected impact of globalization. This effort would be more effective if factors contributing to firm competitiveness are known in advance. This paper provides empirical insights into factors affecting the competitive position of auto-parts suppliers operating in Malaysia. This paper furnishes useful guidelines for the firms in order to remain competitive in the open market mechanism and for better public-private partnership in the automobile industry. A multiple regression analysis of primary data showed that two internal factors – quality and ownership structure, pose significant influence on the competitive position of auto-parts enterprises. Hence, any public-private partnership drive to develop the sector, especially the small and medium enterprises (SMEs), should be devoted to these two assets.